Efficacy and Safety of Treatment With Ferric Carboxymaltose in Patients With Cirrhosis and Gastrointestinal Bleeding - Ballester-Clau, Raquel; Torres Vicente, Gisela; Cucala Ramos, Mercedes; Aracil Blanch, Carles; Miñana Calafat, Josep Maria; Pijoan Comas, Eva; Reñé Espinet, Josep Maria; Planella de Rubinat, Montse (Frontiers in Medicine, 2020)
Background: Patients with liver cirrhosis and gastrointestinal bleeding (GIB) often develop anemia. Ferric carboxymaltose (FCM) is an intravenous (i.v.) iron formulation approved for use in patients with iron deficiency with inadequate response to oral iron therapy or when oral iron cannot be used. Here we analyzed the efficacy and safety of FCM treatment in cirrhotic patients with anemia and GIB. Methods: Retrospective observational study of patients with cirrhosis and acute or chronic GIB treated with 1000 mg FCM at the Hospital Universitari Arnau de Vilanova (Lleida, Spain) that follows a restrictive-transfusion strategy. All data were obtained from the patients’ medical records. We used the Wilcoxon test to evaluate statistical significance. Results: Patients with cirrhosis and GIB (n=34) were treated with 1000 mg FCM. Portal hypertension were present in 88.2% of the patients. For hospitalized patients (n=21), median serum hemoglobin (s-Hb) levels increased by 3.0 g/dL (p<0.02) and 3.9 g/dL (p<0.07) for patients treated with FCM who had or had not received also a transfusion, respectively, compared to levels recorded upon admission. For outpatients (n=13) the mean s-Hb levels was 9.8±1.6 g/dL before FCM treatment and 11.3±2.1 g/dL after treatment, demonstrating a mean increase of 1.5 g/dL (p<0.001). No serious adverse reactions to FCM were observed. Conclusion: FCM administration achieved optimal s-Hb levels in most cirrhotic patients with acute or chronic GIB, suggesting that early FCM infusion improves and maintains optimal s-Hb levels in these patients and may be an appropriate first-line therapy to treat their anemia.